Levels of Satisfavtion in Vocational and General Secondary School Students with Online Learning during the COVID-19 Pandemic: A Case Study from Noth Macedonia - Driton Maljichi; Arwid Hall (University of Sofia, 2022)
The COVID-19 pandemic transferred the entire education system across the world from the physical presence of learning to online learning. Nobody was spared from this, starting from children in primary and secondary schools, as well as university students at faculties. Especially for the primary and secondary education sector, where physical presence is more important due to the young age of school children, this rapid transition to online learning posed challenged to both teachers as well as school students. The aim of this study is to obtain a snapshot of the level of satisfaction by school students with online learning in general education (gymnasium) and vocational schools as well as explore some of the associated challenges they occurred when learning online from home. This research was conducted in the Republic of North Macedonia, specifically in the city of Kumanovo and the neighbouring settlement of Lipkovo The methodology of the research is quantitative, whereby 301 respondents took part in this research, of which 141 from two gymnasiums, and 161 from two vocational secondary schools. Based on the data that was collected, it can be concluded that most of the students from gymnasiums and vocational schools are not satisfied with online learning and prefer learning with physical attendance.